Authorizations for maritime law enforcement operations. (18th August 2017) - McLaughlin, Rob
Abstract: Although there are areas of uncertainty and overlap, authorizations for maritime law enforcement operations are beholden to a different regime from that which governs the conduct of armed conflict at sea. This article seeks to briefly describe five regularly employed authorizations for maritime law enforcement operations at sea: flag State consent, agreed pre-authorization, coastal State jurisdiction, UN Security Council resolutions, and the right of visit.